Empowering the Educational Ecosystem: A Humanistic Approach to Principal Supervision in Vocational Schools - Gugun Gunadi; Teguh Prasetyo; Radif Khotamir Rusli; Zahra Khusnul Lathifah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Principal supervision in Indonesian vocational high schools (SMKs) often remains administrative and compliance-oriented, limiting teacher development and fostering a disempowering educational environment. This study reconceptualizes supervision through a humanistic lens, emphasizing empowerment over control, based on Carl Rogers’ person-centered philosophy. A mixed-methods approach was employed, combining quantitative and qualitative techniques. The study surveyed 160 certified principals from vocational schools in Bogor Regency, Indonesia, using validated instruments measuring servant leadership, principal personality (Big Five traits), organizational climate, and organizational culture. Quantitative data were analyzed using path analysis within a structural equation modeling (SEM) framework. Subsequently, the SITOREM (Scientific Identification Theory for Conducting Operations Research on Education Management) technique was used to prioritize areas for supervisory improvement through expert judgment. All four variables showed significant positive effects on supervision effectiveness. Principal personality had the strongest direct effect (β = 0.363), followed by organizational climate (β = 0.300), servant leadership (β = 0.273), and organizational culture (β = 0.181). SITOREM analysis identified key areas for improvement, including enhancing collaborative supervision practices and strengthening principals' emotional stability and social engagement. Findings highlight the centrality of principal personality and a supportive school climate in empowering teachers. The study introduces the POP-SDM model—a humanistic, data-driven framework for optimizing supervision practices. This model offers a scalable solution for fostering professional autonomy, psychological safety, and self-actualization among educators, ultimately enhancing student outcomes and the broader educational ecosystem.